2018
DOI: 10.7717/peerj.5737
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between neuropsychological and antisaccade measures in multiple sclerosis patients

Abstract: BackgroundThe Stroop test is frequently used to assess deficits in inhibitory control in people with multiple sclerosis (MS). This test has limitations and antisaccade eye movements, that also measure inhibitory control, may be an alternative to Stroop.ObjectivesThe aim of this study was twofold: (i) to investigate if the performance in the antisaccade task is altered in patients with MS and (ii) to investigate the correlation between performances in neuropsychological tests, the Stroop test and the antisaccad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 67 publications
0
6
0
2
Order By: Relevance
“…Thirdly, examining one behaviour (the saccade) within the one sensorimotor system (the ocular motor system) eliminates confounds that might arise from tasks using different sensorimotor modalities (e.g., button presses). Fourthly, and perhaps most important, the antisaccade offers advantages over other typically used measures of inhibition involving multiple cognitive domains (e.g., STROOP), allowing for a more selective examination of attentional control 17 . Finally, as our two tasks are identical at the behavioural level (both require an eye movement toward a peripheral www.nature.com/scientificreports www.nature.com/scientificreports/ location), we are able to examine how sleep and circadian timing impact low-level (bottom up, stimulus-driven) and high-level (top down, goal-directed) attentional control in the absence of many task confounds.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thirdly, examining one behaviour (the saccade) within the one sensorimotor system (the ocular motor system) eliminates confounds that might arise from tasks using different sensorimotor modalities (e.g., button presses). Fourthly, and perhaps most important, the antisaccade offers advantages over other typically used measures of inhibition involving multiple cognitive domains (e.g., STROOP), allowing for a more selective examination of attentional control 17 . Finally, as our two tasks are identical at the behavioural level (both require an eye movement toward a peripheral www.nature.com/scientificreports www.nature.com/scientificreports/ location), we are able to examine how sleep and circadian timing impact low-level (bottom up, stimulus-driven) and high-level (top down, goal-directed) attentional control in the absence of many task confounds.…”
Section: Discussionmentioning
confidence: 99%
“…We, and others, have utilised the antisaccade task to measure attentional inhibitory control with different clinical disorders and/or under different task conditions [15][16][17][18][19] . The task requires the participant to inhibit a reflexive response toward a peripheral visual stimulus, and instead direct their gaze to the mirror opposite location.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies showed the same good relationship between the AS responses and neuropsychological measures of EFs in clinical populations (Hutton, 2008;Heuer et al, 2013) that typically showed executive impairments, such as dementia (Boxer et al, 2006) and schizophrenia (Hutton et al, 2004;Levy et al, 2004). Recently, Ferreira and colleagues showed that patients with MS have higher error rates and prolonged latency than controls in the AS parameters (Ferreira et al, 2018). Thus, AST may be a selective and independent measure to investigate inhibitory control in MS.…”
Section: Eye Trackersmentioning
confidence: 99%
“…Saccadic velocity is not subject to voluntary control (Leigh & Zee, 1999), unlike saccadic amplitude or fixation duration. Thus it represents the underlying neural activity more accurately than other gaze parameters (Bower et al, 2005;Ferreira et al, 2017). Saccadic eye movements and their neurological control signals change significantly as the human subject fatigues.…”
Section: Introductionmentioning
confidence: 99%